The Role of Moral Reasoning, Emotional Intelligence on Fraud Intention: Applied on Auditor Profession in Indonesia - Irmayanti Sudirman (www.amertainstitute.com, 2024)
This research investigates the role of moral reasoning and emotional intelligence on fraud intention as applied to the auditor profession in Indonesia. The auditor profession has a role and responsibility in maintaining the integrity of a company's financial reports. If the auditor has the intention to carry out an incident, then the quality of the resulting financial reports will be checked and this could be detrimental to many parties. The goal of this research is to decide whether there is a relationship between emotional intelligence, moral reasoning and fraud intention in the auditor profession in Indonesia. This research methodology uses quantitative descriptive and data analysis using SEM PLS version 4.0. Data collection distributes questionnaires using a google form link and sends them to auditors or KAP offices in Indonesia. The research results show that emotional intelligence has a significant effect on fraud intention, Moral reasoning has a significant effect on fraud intention, Emotional intelligence has a significant effect on moral reasoning, and then moral reasoning mediates a significant relationship between emotional intelligence and fraud intention. Strong moral reasoning will encourage auditors to act in accordance with ethical and legal values, thereby reducing the occurrence of dishonest actions. On the other hand, individuals with weak moral reasoning tend to be more easily tempted to commit fraud, especially when faced with pressure or large profits. Meanwhile, emotional intelligence allows auditors to better manage emotions such as stress, pressure and temptation. Auditors with high emotional intelligence tend to be better able to refrain from impulsive actions and make rational decisions, even in difficult situations. In other words, strong moral reasoning and high emotional intelligence can be an effective defense against fraud intentions.